2009
DOI: 10.1021/jp809839t
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Near Infrared Spectroscopy and Vibrational Dynamics of Dideuteromethane (CH2D2)

Abstract: We report the infrared spectrum of CH(2)D(2) measured in the range from 2800 to 6600 cm(-1) with the Zurich high-resolution Fourier transform interferometer Bruker IFS 125 prototype (ZP 2001, with instrumental bandwidth less than 10(-3) cm(-1)) at 78 K in a collisional enclosive flow cooling cell used in the static mode. Precise experimental values (with uncertainties between 0.0001 and 0.001 cm(-1)) were obtained for the band centers by specific assignment of transitions to the J = 0 level of 71 vibrational l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 82 publications
3
38
0
1
Order By: Relevance
“…[51][52][53][54]), which correlates with the main statements of the general rotation-vibration theory, Ref. [39].…”
Section: Ro-vibrational Analysis Of the ðVsupporting
confidence: 71%
“…[51][52][53][54]), which correlates with the main statements of the general rotation-vibration theory, Ref. [39].…”
Section: Ro-vibrational Analysis Of the ðVsupporting
confidence: 71%
“…We mention here the first observation of infrared spectra of nanoparticles of HF/DF in supersonic jets by Quack et al (1997). The high-resolution advantage of our spectrometers in the higher frequency regions is illustrated using the methane spectra (Albert et al 2009b) shown in Figure 12 and in the spectra of isotopomers of methane discussed in Niederer et al (2008) and Ulenikov et al (2009Ulenikov et al ( , 2010b. Figure 12 displays the FTIR methane 12 CH 4 spectrum in the range 2700 up to 7700 cm −1 recorded in the collisional cooling cell at 80 K. The resolution defined here as 1/d MOPD ranging from 0.0027 to 0.005 cm −1 was chosen so that it was half of the Doppler width or less in the spectral range measured.…”
Section: Co and Ch 4 Ftir Spectra Under Collisional Cooling Conditionsmentioning
confidence: 85%
“…It is constructed of stainless steel, has a base optical length of 0.625 m, and offers maximum path lengths of 15-20 m. This cell can be immersed in either liquid nitrogen or liquid helium depending on the desired temperature regime, and is fitted with heaters and thermostats to achieve continuous intermediate temperatures from 4 to 79 K when using liquid helium [78,79], and from 79 to 300 K with liquid nitrogen [80][81][82][83][84][85][86]. In addition, the EFC is equipped with a series of solenoid gas inlet valves (which can be operated in pulse or continuous mode), and with single and multiple injection nozzle devices.…”
Section: Australian Synchrotronmentioning
confidence: 99%